2018
DOI: 10.1038/s41746-017-0002-4
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of remote patient monitoring on clinical outcomes: an updated meta-analysis of randomized controlled trials

Abstract: Despite growing interest in remote patient monitoring, limited evidence exists to substantiate claims of its ability to improve outcomes. Our aim was to evaluate randomized controlled trials (RCTs) that assess the effects of using wearable biosensors (e.g. activity trackers) for remote patient monitoring on clinical outcomes. We expanded upon prior reviews by assessing effectiveness across indications and presenting quantitative summary data. We searched for articles from January 2000 to October 2016 in PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 52 publications
3
153
0
Order By: Relevance
“…Remote monitoring technologies can connect wirelessly to networks via Bluetooth, WiFi, or cellular connection. An extensive body of literature exists regarding the use of DH in the remote monitoring of chronic diseases [33,34]. The same concept could also be applied to the monitoring of infectious diseases.…”
Section: Monitoringmentioning
confidence: 99%
“…Remote monitoring technologies can connect wirelessly to networks via Bluetooth, WiFi, or cellular connection. An extensive body of literature exists regarding the use of DH in the remote monitoring of chronic diseases [33,34]. The same concept could also be applied to the monitoring of infectious diseases.…”
Section: Monitoringmentioning
confidence: 99%
“…For balance, caution should be used in understanding the current state of digital biomarkers, as several studies reported in the literature are uncontrolled, underpowered studies. Recently, a meta‐analysis evaluating the impact of remote monitoring devices such as wearables for patient monitoring or improving clinical outcomes showed no impact of these devices on clinical outcomes such as BMI, blood pressure, or waist circumference . However, the authors noted that the studies were vastly heterogeneous in their design, device type, and outcomes.…”
Section: Home Sampling Of Digital Biomarkers or Physiological Pk/biommentioning
confidence: 99%
“…Recently, a meta-analysis evaluating the impact of remote monitoring devices such as wearables for patient monitoring or improving clinical outcomes showed no impact of these devices on clinical outcomes such as BMI, blood pressure, or waist circumference. 40 However, the authors noted that the studies were vastly heterogeneous in their design, device type, and outcomes. This points overall to substantial gaps in the broader evidence base.…”
Section: Home Sampling Of Digital Biomarkers or Physiological Pk/biommentioning
confidence: 99%
“…Moreover, the added value of remote monitoring of physical activity on clinical outcome is unknown. A recent meta-analysis by Noah et al [4] suggested that remote activity programs resulted in small increases in activity in overweight or obese patients. Furthermore, in the evergrowing activity trackers market, it is unclear which consumer activity trackers are sufficiently reliable to be used for remote monitoring rather than for wellness or sports purposes.…”
Section: Introductionmentioning
confidence: 99%